(untitled) (Journal of Academic Research, 2025)
Background: consanguinity is defined as a union between second cousins or closer with an inbreeding coefficient greater than or equal to 0.0156. Consanguinity is practiced by up to 10% of the global population, with rates ranging from 80.6% in certain Middle Eastern provinces to less than 1% in Western societies. METHODS: A cross-sectional study was conducted in MISRATA CITY – LIBYA between January 2024 and January 2025 to determine the impact of consanguineous marriages on offspring health. Filling prepared questionnaire (copy attached) with direct interviewing of random sample of parents attending Misurata Medical Centre for any reasons. Ethical considerations: formed consent from one of the parents and consent from the ethical committee at Misurata Medical Centre Results: In our study, parental consanguinity was associated with a higher likelihood of consanguineous unions. the education level between the wives varying between elementary (25%), high school (18%), bachelor (30%) while on the other hand for the husbands the education level were, elementary (33%), diploma & technical institution (34%), bachelor (20%) which reflect the focusing skilled education for the males. Women marriage before age 23 was significantly higher than that of their late marrying counterparts. On the other hand, men have a significantly higher likelihood (1.99 times) of contracting consanguineous unions between the ages of 23 and 29.